Relationship between the financial indicators and the implementation of telework - Miroslava Vlčková; Zuzana Frantíková; Jaroslav Vrchota (DANUBE: Law, Economics and Social Issues Review, 2019)
In most European countries, teleworking or homeworking is used in various forms that differ from one another by its legal regulation. The paper examines the SME's in the Czech Republic from the perspective what makes them to adopt telework using the financial indicators. We hypothesized that employer adoption of telework would depend on some economic factors. The empirical evidence showed that a typical company that uses telework is a company with higher ratio of liabilities and therefore lower ratio of equity, a lower ratio of fixed assets, higher sales, lower inventory, higher labour productivity and higher value added per employee, higher return on equity, higher personnel costs, higher average wages. Within the analysed enterprises, 16 indicators were assessed; the 9 indicators showed the difference between companies that use telework and companies that do not use telework. The research shows a typical company that uses telework.
Keywords: 330; Telework; SME's; Financial and Economic Indicators; Mann-Whitney U test